ANALISIS YURIDIS AKIBAT HUKUM DARIBUKU DAFTAR AKTA NOTARIS YANG TIDAK DITANDATANGANI DAN DI PARAF KEPADA MAJESLIS PENGAWAS DAERAH - JUNITA TAMPUBOLON (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Notaris Dr. Suprayitno, SH, MKn2. Notaris Dr. Henry Sinaga, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum Article 58, figure 1 of Law No. 2/2014 on the Amendment of Law No. 30/2004 on Notarial Position states that a Notary makes the list of deeds, the list of underhanded documents, the list of booked and underhanded deeds, and the other documents required by the laws. The list of deeds is a monthly report to the MPD (Regional Supervisory Council) in a Notary’s work place. The research used juridical normative method. Secondary data were obtained from primary, secondary, and tertiary legal materials. They were gathered by conducting library research, field research, documentary study, and interviews. The result of the research shows that the task and authority of MPD are organizing meetings to identify whether there is violation against the Code of Ethics by a Notary or against Notarial implementation.Keywords: Book of the List of Deeds, MPD (Regional Supervisory Council)